Non-linear Optimization Model for Furrow Irrigation System in Maize Crop - Garg, Sunil; Jain, A K; Kaushal, M P; Gulati, H S (Journal of Agricultural Engineering, 2009)
Nonlinear optimization design models were developed for field conditions to design and manage furrow irrigation system using Lewis-Kostiakov infiltration equation. The design criterion used in the models was the depth of irrigation and basic infiltration rate of the soil. The objective function of the non-expanded nonlinear model was constructed on the basis of a relationship between net returns and water requirement efficiency, and the expanded nonlinear model was developed in terms of net returns and costs. The design variables of the models were the inflow rate, length of run, inflow time, number of furrows per set and number of sets. The expanded nonlinear model gave a better representation of the design parameters and was more flexible because it permitted easy changes in the objective function than non-expanded nonlinear model. The model can be used to compare different types of furrow irrigation management strategies.